2005
DOI: 10.1108/01443570510608583
|View full text |Cite
|
Sign up to set email alerts
|

Model for manufacturing strategic decision making

Abstract: Purpose -Proposes a model of strategic planning as a basis to overcome the identified shortcomings in the past empirical research. The basic assumption of the proposed model is that an appropriate strategic analysis is necessary in order to ensure appropriate strategic decisions. Design/methodology/approach -Shortcomings related to empirical research in the past were identified with the aim of discussing some possible reasons why the concept of manufacturing strategy had not been more widely adopted in practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
(47 reference statements)
0
12
0
5
Order By: Relevance
“…Em decorrência disso, espera-se de todas as áreas da empresa, e principalmente da manufatura, um papel ativo nesse jogo não apenas de apoio à estratégia corporativa, mas se tornando uma vantagem competitiva através do correto alinhamento na escolha e desenvolvimento de sua estratégia de operação (RUDBERG; WEST, 2008;RUSJAN, 2005;SUN;HONG, 2002;PORTER et al, 1999).…”
Section: A Manufaturaunclassified
“…Em decorrência disso, espera-se de todas as áreas da empresa, e principalmente da manufatura, um papel ativo nesse jogo não apenas de apoio à estratégia corporativa, mas se tornando uma vantagem competitiva através do correto alinhamento na escolha e desenvolvimento de sua estratégia de operação (RUDBERG; WEST, 2008;RUSJAN, 2005;SUN;HONG, 2002;PORTER et al, 1999).…”
Section: A Manufaturaunclassified
“…Borut Rusjan (2005) most researchers agree that the main emphasis of strategic decision making is on ensuring the achievement of competitive advantage of an enterprise. Harrison (1975) suggested that the merger of technical and human factors into the managerial decision-making process is the key to successful decision making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Borut Rusjan (2005) states that business strategy specifies the scope of each business and defines the basis on which a business unit can achieve and maintain a competitive advantage within its industry…”
Section: Introductionmentioning
confidence: 99%
“…By going beyond only determining significant relationships between resource investments and performance, the empirical model seeks to examine those operational resources that can be leveraged by managers in resource deployment to improve manufacturers' performance (cf. Rusjan, 2005). The empirical model is illustrated in Figure 1.…”
Section: Empirical Modelmentioning
confidence: 99%